Investigating the correlation of self-care and quality-of-life patients with heart failure - Leili Tapak; Payam Amini; Sharareh Parami; Omid Hamidi; Vajiheh Ramezani-Doroh; Azim Azizi (BMC Cardiovascular Disorders)
Abstract Background Heart Failure adversely affects the patients’ quality-of-life. Quality-of-life in patients with heart failure is related to their self-care and other factors. This study aimed to investigate the correlation of quality-of-life and self-care among patients with heart failure and to determine their associated factors. Methods This descriptive-correlational study was conducted on 217 patients with heart failure at the Farshchian Heart Hospital in Hamadan, Iran, from April 13, 2022, to March 29, 2023. Patients completed the self-care questionnaire for patients with heart failure and the Minnesota quality-of-life questionnaire. A quantile regression model was used to identify factors related to self-care and quality-of-life in patients with heart failure. Analysis was done using R.4.4.0 (P < 0.05). Results The mean(± SD) of age, quality-of-life and self-care were 62.16(± 7.86), 60.05(± 8.85), and 35.16(± 5.36), respectively, indicating a low level of quality-of-life and moderate level of self-care. There was no significant correlation between self-care and quality-of-life(r = 0.007; P = 0.916). The correlates of self-care which were significant in almost all Deciles included duration of disease(P < 0.05 for 4th and 5th deciles and P < 0.001 for other deciles), gender(P < 0.01 for the 1st,7th,8th,9th deciles and P = 0.017 for 2nd ), education (P < 0.001), income(P < 0.05 for 3rd -7th deciles and P < 0.001 for 8th and 9th deciles), substance abuse (P = 0 < 0.001 to P = 0.047 for various deciles), and history of hypertension (P < 0.05). Moreover, for the quality-of-life the associated variables included duration of disease (P < 0.001 for the 1st to 5th deciles and P = 0.028 for the 8th decile), sufficient income (P:0.001, 0.004, 0.018, 0.026,<0.001, and < 0.001 for the 2nd, 3rd, 5-6th, and 8-9th deciles). Conclusion The non-significant correlation between self-care and quality-of-life shows that lower self-care is linked to a diminished quality-of-life. Patients motivated to engage in self-care are likely to experience fewer hospital readmissions and an improved quality-of-life. Healthcare providers/policymakers should be aware of the importance of self-care in patients with heart failure and help promote their quality-of-life by enhancing their self-care behavior through personalized interventions as own efforts to prevent further worsening of HF. Specifically, such interventions should consider the multifactorial nature of these outcomes and the diverse demographic, socio-economic, and health-related characteristics of this population.